TOWARDS A CONCEPTUAL FRAMEWORK OF ISLAMIC LEADERSHIP SUCCESSOR’S ATTRIBUTES MODEL AND GOOD GOVERNANCE - Alsarhi, Naji Zuhair (Journal of Techno-Social, 2015)
The purpose of this paper is to propose a conceptual model that explains the relationship between Islamic leadership successionpersonalityattributes and good governance. The paper sources information from an extensive search of literature to design a conceptual model of Islamic leadership succession (personal attributes & governmental characteristics of Succession) and good governance. The model will provide an integration of relationships that will add valuable insights into improved leadership succession theory in the related literature. The paper may assist particularly policy makers and strategists to focus on new possibilities of leadership successors attributes that will lead to improved governance as well as government performance in the world in general, and the Palestine community, in particular.